2020
DOI: 10.1002/ece3.6869
|View full text |Cite
|
Sign up to set email alerts
|

High parasite diversity in the amphipodGammarus lacustrisin a subarctic lake

Abstract: There is often more than meets the eye when examining food web ecology. Network concepts such as connectance (Lafferty et al., 2006) and robustness (Lafferty & Kuris, 2009) have been well described for several food webs, including webs that consider infectious agents. Here, we look at a key species in the consumer dynamics of the Norwegian subarctic lake Takvatn (hereafter "Takvatn"; "vatn" means "lake" in Norwegian), the amphipod Gammarus lacustris, and reveal that it plays a central role in parasite transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…In southwestern Nova Scotia, emerging brook trout fry (as a cohort) acquired parasites within the first month post-emergence either through: 1) free swimming infective copepodids of S. edwardsii (see White et al 2020); 2) adult G. colemanensis transferring directly between fish (see Cusack 1988, 1989); or 3) food-borne infective stages of E. lateralis (cystacanths) and Crepidostomum sp. (metacercariae) using amphipod/mayfly larva as intermediate hosts (Baggs and Cowan 1989, Caira 1989, Shaw et al 2020. This early acquisition of parasites should be expected given that fry live sympatrically with older cohorts in these streams and are essentially proximal to parasites cycling through older cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In southwestern Nova Scotia, emerging brook trout fry (as a cohort) acquired parasites within the first month post-emergence either through: 1) free swimming infective copepodids of S. edwardsii (see White et al 2020); 2) adult G. colemanensis transferring directly between fish (see Cusack 1988, 1989); or 3) food-borne infective stages of E. lateralis (cystacanths) and Crepidostomum sp. (metacercariae) using amphipod/mayfly larva as intermediate hosts (Baggs and Cowan 1989, Caira 1989, Shaw et al 2020. This early acquisition of parasites should be expected given that fry live sympatrically with older cohorts in these streams and are essentially proximal to parasites cycling through older cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…An initial screening of parasite species present in the benthic web was obtained from continued annual parasite sampling through the long-term studies of the fish populations with occasional observations of parasites present in other organisms up to 2010 (Amundsen et al 1997 ; Knudsen et al 2001 ; Klemetsen and Knudsen 2013 ; Thieltges et al 2013 ; Kuhn et al 2016b ; Henriksen et al 2019 ; Prati et al 2020b ). However, the majority of information on parasites in the lake originates from 2012 to 2015 (with some additional sampling up to 2018), when the benthic invertebrate community, including arthropods, annelids, and mollusks, was more extensively sampled and screened for parasites (see Soldánová et al 2017 ; Shaw et al 2020 ). Helminths and other macroparasites have been thoroughly explored in our parasite surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Studying the pelagic food web, Amundsen et al ( 2009 ) addressed how parasites affected food-web structure and complexity, and Amundsen et al ( 2013 ) examined how two fish introductions affected pelagic food-web topology and increased parasite diversity. Since those studies, additional work in the system has shown that the benthic compartment has a distinct set of free-living and parasitic taxa from the pelagic web (e.g., Kuhn et al 2015 ; Frainer et al 2016 ; Soldánová et al 2017 ; Shaw et al 2020 ; Prati et al 2021 ). Here, we contrast key food-web metrics in each of Takvatn’s distinct compartments as well as the whole Takvatn system to understand how parasites affect food-web topology in a subarctic lake and to compare the pelagic and benthic food webs’ topology when including parasites.…”
Section: Introductionmentioning
confidence: 99%
“…They act as detritivores, shredders, suspension feeders, scavengers, parasites or predators (Kaestner 1967, MacNeil et al 1997, Ruffo et al 1998) -and constitute an important food source for fish. Some species are intermediate hosts to acanthocephalan parasites (Westram et al 2011, Shaw et al 2020, some are hosts to ciliates (Gudmundsdóttir et al 2018) or temnocephalid flatworms (Matjašič 1990), while several species live in associations with other animals, such as other crustaceans, bryozoans, mollusks, or cnidarians (Lörz et al 2014, Vader & Myers 1993, Vader & Tandberg 2013, 2020. Because of the absence of dispersal larvae (Myers & Lowry 2009), many species are narrow endemics (Trontelj et al 2009, Bregović et al 2019, Esmaeili-Rineh et al 2020) and an important part of natural heritage.…”
Section: Introductionmentioning
confidence: 99%